The Pedagogy of Alternation in pomerana community of Santa Maria de Jetibá, Espírito Santo, Brazil - Edineia Koeler; Erineu Foerste; Alberto Merler (Universidade Federal do Norte do Tocantins, 2019)
The article analyzes aspects of the Alternation Pedagogy, understood from Nosella's perspective (1977, 2012), and its relationship with Pomeranian culture. It takes as its study object the Emílio Schroeder State School, located in Alto Santa Maria, Santa Maria de Jetibá, Espírito Santo, Brazil, to understand how such a community, with a significant presence of the traditional Pomeranian people, comprises the alternation project. With a qualitative-descriptive approach, it benefits from narratives of a teacher-monitor with significant experience in Agricultural Family Schools and, in addition, analyzes a set of documents consisting of 52 questionnaire forms applied in 2011 to student's families. The interpretative treatment of the responses to four items of this instrument showed that, after a decade of the implementation of the alternation regime in school, which occurred in 2001, and it was not the parents who responded to this instrument the same who fought for the alternation regime in the school. There have been changes in the meaning given by families and the wider community to this educational model in the social context analyzed. It is noteworthy that the cultural and identity dimensions of the traditional Pomeranian people can contribute to the problematization of the school project; whereas the initiative of rural communities is fundamental for the conquest and permanence of alternative projects in rural education; that parent's poor education may have immediate repercussions on schoolwork, but it does not prevent them from seeking quality education for their children.